896 Improving Intravenous Fluid Therapy to Reduce the Incidence of Acute Kidney Injury in Hip Fracture Patients. (4th May 2021) - McCann, C; Hall, A; Leow, J M; Harris, A; Hafiz, N; Myers, K; Amin, A; MacLullich, A
Abstract: Background: Acute kidney injury (AKI) in hip fracture patients is associated with morbidity, mortality, and increased length of stay. To avoid this our unit policy recommends maintenance crystalloid IV fluids of > 62.5mL/Hr for hip fracture patients. Method: Three prospective audits, each including 100 consecutive acute hip fracture patients, were completed with interventional measures employed between each cycle. Data collection points included details of IV fluid administration and pre/post-operative presence of AKI. Interventions between cycles included implementation of admission/post-take checklist tools and various educational measures for Emergency Department, nursing and admitting team staff with dissemination of infographic posters, respectively. Results: In cycle one and two, many patients received inadequate fluids (46/100 and 56/100 respectively). There was no significant difference in the incidence of AKI between patients receiving adequate or inadequate fluid in either cycle (p < 0.05). In cycle three, more patients received adequate fluids (79/100, p < 0.05). Patients prescribed adequate fluids were less likely to develop post-operative AKI (2/79, 2.5% vs 3/21, 14.3%; p < 0.05). Discussion: This audit demonstrates the importance of administering appropriate IV fluid in hip fracture patients to avoid AKI. Improving coordination with Emergency Department and ward nursing/medical ward staff was a critical step in improving our unit's adherence to policy.